Footprints of sorrow - Porres, Alfonso; Bullfrog Films; Television Trust for the Environment; TVE International (Oley, PA : Bullfrog Films, 1995)
Documents how Guatemalan women widowed in the civil unrest have conducted literacy classes and encouraged political participation through the formation of the organization, Conavigua.
Series producer, Emily Marlow.
Spanish with English subtitles.
Keywords: Conavigua (Organization); War widows -- Political activity -- Guatemala; Women political activists -- Guatemala -- Interviews; Women -- Guatemala -- Social conditions